Behind the Defeat of Local Incumbents: A Systematic Review of Economic Voting, Patronage, Party Conflict, and Electoral Accountability in Democratic Elections - Iyan Maulana Amnum Al Amin; Kushandajani (Dinasti Research, 2026)
Local elections constitute a crucial arena for democratic accountability because local governments control public services, welfare distribution, public expenditure, bureaucratic appointments, and access to state resources. Yet local incumbents sometimes lose despite possessing the structural advantages of office. This systematic review synthesizes 48 studies identified through Scopus and related bibliographic checking to explain why such defeats occur. Using a mechanism-based qualitative synthesis, the review integrates evidence from studies on economic voting, patronage and clientelism, party organization, candidate selection, opposition coordination, electoral integrity, institutional trust, and democratic alternation. The synthesis shows that local incumbent defeat is rarely caused by a single factor. Economic voting matters when citizens can attribute unemployment, welfare retrenchment, fiscal choices, crisis response, or service delivery to incumbents. Patronage may protect incumbents when networks remain credible and morally legitimate, but it may also generate backlash when voters associate distributive politics with corruption, arrogance, exclusion, or manipulation. Party conflict and candidate selection may weaken incumbents before the general election, especially when nomination rules, factional competition, elite bargaining, or opposition coordination reduce campaign capacity. Ultimately, incumbent defeat becomes democratically meaningful only when electoral institutions are credible, losing actors concede defeat, and transitions preserve governmental continuity. This review provides an integrated framework that treats local incumbent defeat as both an electoral outcome and a governance process.